181k views
4 votes
Simplify this expression.

6x2(3x)

User TylerW
by
5.3k points

2 Answers

5 votes

36x

6*2(3x)

6*6x multiply 2 and 3x to get 6x

36x multiply 6*6x to get 36x

User BhejaFry
by
5.5k points
3 votes

For this case we must simplify the following expression:


6x ^ 2 (3x)

We have to:


6 * 3 = 18

By definition of multiplication of powers of equal base we have that the same base is placed and the exponents are added:


a ^ n * a ^ m = a ^ {n + m}

So:


x ^ 2 * x = x^(2 + 1) = x ^ 3

Finally we have:


6x ^ 2 (3x) = 18x ^ 3

Answer:


18x ^ 3

User Kirk Munro
by
5.4k points